Neurofibromatosis-Noonan syndrome: a prospective monocentric study of 26 patients and literature review - Didier Bessis; Dominique Vidaud; Pierre Meyer; Laurence Pacot; de La Villeon G; Adeline Alice Bonnard; Yline Capri; Christine Coubes; Fanchon Herman; Didier Lacombe; Nicolas Molinari; Laura Poujade; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Data on clinical manifestations of neurofibromatosis-Noonan syndrome (NF-NS) remain heterogeneous, with limited validated descriptions. Methods This study aims to better define the clinical and molecular features of NF-NS and compare them with existing literature. Secondary objectives include evaluating inter-rater diagnostic agreement among experienced clinicians and assessing the utility of deep-learning algorithms (Face2Gene® [F2G]). Additionally, we assess the prevalence of congenital heart malformations (CHM) in NF-NS compared to ‘classic’ neurofibromatosis type 1 (NF1). A 9-year, prospective, monocentric study was conducted, involving patients with NF1 pathogenic variants (PVs) and Noonan syndrome-like facial phenotype (NSLFP). Results Twenty-six patients were enrolled. NSLFP was categorized as ‘suggestive’ in 69% of cases and ‘typical’ in 31%. The presence of at least two facial abnormalities (e.g., low-set ears, downslanted palpebral fissures, hypertelorism, and ptosis) was consistently observed in ‘typical’ cases. Inter-rater concordance was substantial (0.65 [95% CI = 0.56; 0.74]), while concordance between clinicians and F2G was almost perfect at (0.821 [CI 95% = 0.625; 1.000]). Missense NF1 PVs were observed in 38.5% of cases. Apart from NSLP and a high frequency of pectus excavatum (62.5%), no significant differences in anthropometric, dermatological, neurological, skeletal, or ocular clinical features were observed between NF-NS and ‘classic’ NF1. CHM were found in 19.2% of NF-NS patients, with pulmonic stenosis present in 7.7%. Conclusion NF-NS is a distinct phenotypic variant of NF1, marked by NSLP with consistent facial features -, and frequent pectus excavatum. F2G demonstrated high diagnostic concordance, reinforcing its clinical utility. Given the elevated risk of CHM, especially pulmonic stenosis, proactive cardiovascular assessment similar to other RASopathies is recommended for NS-NF patients, regardless of NF1 PV type.